Improving Listening Comprehension Using Practical Techniques in the English Third and Fourth Levels - Heredia, María Augusta (Kronos – The Language Teaching Journal, 2018)
Though listening is fundamental to the acquisition of the English language, there has been little research about this skill. This experimental research describes listening techniques to improve students’ listening comprehension. The targeted population consisted of university students in pre-intermediate level in a university in Ecuador. Students with poor listening skills were detected in the pre-test and teacher observation. Likewise, the background of the study showed that the lack of listening teaching and meagre listening habits were the cause of diminishing listening skills. The treatment was given to 15 students (the experimental group). It consisted of listening techniques based on methodology (note-taking, dictogloss, and dictation) and listening activities based on assessment (matching, multiple matching, sentence completion exercises). Data was gathered by means of questionnaires, interviews, the pre-test and the post-test. Finally, post intervention data demonstrated the experimental group students’ listening progress. On the whole, the results showed that the treated group increased their listening skills due to the listening techniques applied.